Law and Violence - García Blanco, José María (Política y Sociedad, 2011)
The relationship between law and violence has been analyzed traditionally within the framework of the reflection on law’s foundation. The article reviews the most important theoretical moments in the history of the analysis of law’s foundation and the role of violence, and then focuses on the authors who have made three of the most important contributions to this analysis in the twentieth century: Benjamin, Derrida and Luhmann. Although all three agree on the paradoxical foundation of law, they differ in their treatment. Benjamin and Derrida made a critique and a deconstruction, respectively, of what they consider the constitutive violence of law, guided by a transcendent idea of justice. Instead Luhmann develops and immanent (sociological) analysis, which leads him to argue that the semantics of violence does not provide useful indications for the analysis of the underlying problem, even distorts it. The article concludes with a reflection that connects the Luhmann’s analysis with the Carl Schmitt’s theory of sovereignty: although antagonists, norm and decision are the basic elements of law, because there is not possibility to establish normative orders without decisions, and the monopoly of the “ultimate decisions”, rather than that of violence, is what ensures the factual normalization required by the regular operation of any normative order.
Keywords: Self-reference; Critique; Decision; Deconstruction; Equity / Justice; Force; Incompleteness; Paradox; Violence.